The Impact of Vendor Relationship Management and Organisational Performance: A Case Study of DHL Express - Harriet Mbabazi (Uganda Christian University, 2024)
The purpose of the study was aimed at assessing the impact of vendor relationship management and organisational performance basing on the following objectives; to examine the challenges faced while managing vendor relationships by organisations, to analyse the strategies employed in order to overcome these challenges, and to assess vendor relationship management and its impact on organisational performance. Both qualitative and quantitative research designs were used. The sample size was randomly selected using the simple random sampling design. A sample size of 33 respondents was considered while secondary information was included too such as textbooks, pamphlets, research reports, journals, magazines, internet and newsletter were used in addition to various company annual reports, and primary data was collected using questionnaires provided to respondents. After data was collected, it was analysed in line with the objectives of the research, research questions and other information especially from the literature review. Frequency tables and graphs were worked out basing on the data entered into excel. In these frequency tables and graphs, analysis was done with a corresponding percentage. Findings revealed that DHL Express to a lesser extent experiences challenges to do with vendor relationship management to which they have comprehensively managed by adopting various strategies in order to overcome these such as vendor selection criteria, communication and collaboration and continued performance monitoring and evaluation so as to overcome challenges such as quality control issues with their vendors and contractual disputes with the same. A positive impact was identified on the performance of the organisation due to a properly managed and consistent relationship with their vendors through continued collaboration and communication while regularly monitoring of the vendors which has resulted into openness and involvement of their vendors in the supply chain motivating them to share their knowledge and insights regarding the improvement of their services and product in the market. Most of the respondents also went ahead to show that the organisation has overall improved their performance at a great extent which has given them have an outstanding competitive edge in their market globally. However, while not every supply chain relationship and process is entirely perfect, it was recommended that the organisation increases their vendor relationship strategies such as enhancement of innovation with their vendors especially in a cutting edge technologically advancing market so as to maximise the streamlining of their activities and increase the innovation, productivity, and performance of the organisation overall.
Undergraduate Research